Freeze-Fracture Studies of Human Blood Platelets Activated by Thrombin Using Rapid Freezing - Hols, Hans; Sixma, Jan J; Leunissen-Bijvelt, J; Verkley, Arie (Thrombosis and Haemostasis, 1985)
In this study the influence of thrombin activation on human blood platelets has been followed by freeze-fracturing electron microscopy using rapid freezing in order to catch the initial changes in shape and the morphological alterations during the process of exocytosis of secretory granules. We found that isolation of the platelets by itself leads to some degree of shape change, which made it impossible to study the resting discoid platelet by rapid freezing.Activation of the platelets by thrombin induced dilation of the “surface connecting system (SCS)” with formation of large vacuoles as a result of fusion of the secretory granules with SCS. No intermediary fusion stages or structures were observed even using rapid freezing. Volcano-like protrusions and the corresponding complementary pits were seen at the SCS. These structures were interpreted by us as fractures through protoplasmic channels crossing the SCS. These channels originate during the swelling of the SCS as a result of the fusion of secretory granules with the SCS.
Keywords: Blood platelets; Freeze; fracture; Secretion